2018
DOI: 10.3390/genes9070328
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Profile Induced by Valproic Acid (VPA) in Pediatric Epileptic Patients

Abstract: Epilepsy is a neuronal disease that affects up to 70 million people worldwide. The development of effective therapies to combat childhood epilepsy requires early biomarkers. Here, we performed a whole-genome microarray analysis in blood cells to identify genes differentially expressed between epileptic and epileptic valproic acid (VPA)-treated children versus normal children to obtain information about the gene expression to help us to understand genetic aspects of this disease. We found that the most signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In the present study, most of the DEGs were implicated in the immune and inflammatory response, and associated with cytokine-cytokine receptor interactions, as also identified in epileptic patients by Floriano-Sánchez et al (32). Inflammation is increasingly recognized as an important pathogenetic factor in epilepsy.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, most of the DEGs were implicated in the immune and inflammatory response, and associated with cytokine-cytokine receptor interactions, as also identified in epileptic patients by Floriano-Sánchez et al (32). Inflammation is increasingly recognized as an important pathogenetic factor in epilepsy.…”
Section: Discussionsupporting
confidence: 81%
“…Subjects aged from 0 to 18 years were enrolled at the Children's Hospital of Fudan University (Shanghai, China) between July 2016 and May 2018. Each patient was evaluated according to the inclusion and exclusion criteria (32). The inclusion criteria were as follows: Pediatric patients diagnosed with epilepsy or an epileptic syndrome and administration of VPA for at least one year.…”
Section: Methodsmentioning
confidence: 99%
“…Experimental and clinical studies show that epilepsy is characterized by many pathogenic mechanisms primarily related to functional alterations in neuronal and neurovascular units and by an imbalance between excitatory (glutamate) and inhibitory ( γ -aminobutyric acid) neurotransmission [7, 8]. Recently, using microarray technology, our group showed that the immune response, inflammation, and oxidative stress (OS) pathways are mainly activated in Mexican epileptic children [9]. Antiepileptic drugs (AEDs) are used to treat epilepsy, and they mainly target ion channels and inhibit neuronal excitability.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that oxidative damage in proteins is a mechanism underlying neurodegeneration [68], and its consequences in epilepsy could be ranged from cell membrane modification to posttranslational modification, specifically alterations in ion channels [66]. In a recent study on epileptic children, our group used microarray technology and observed that epileptic conditions modified the gene expression of many ribosomal proteins and of some GPx and glutathione-S-transferase isoforms and that the principal biological processes with the highest numbers of differentially expressed genes were related to translation, poly(A) RNA and protein binding, and alternative splicing [69]. The above observations confirm that modification of the protein structure and modification of the activity of enzymes related to GSH are the main mechanisms involved in epilepsy progression and that H. inuloides extracts are capable of ameliorating this condition in the epileptic brain.…”
mentioning
confidence: 99%